Exploring Learning by Design to Nurture Joyful Literacy Experiences in a Grade Eight English Language Arts Classroom - Du, Xiaoxiao; Doering, Nicole (Language and Literacy / Langue et littératie, 2025)
This paper details an example of teacher practices that drew upon multiliteracies theory and pedagogy to engage in reflective pedagogical practice and enact transformative teaching and learning in a grade 8 English Language Arts classroom in Manitoba. The meaning of design is discussed, and the learning by design framework is investigated with a focus on knowledge processes (Cope & Kalantzis, 2015). Findings affirm teachers as designers, recognize students as creative meaning makers, and celebrate teacher empowerment, student agency, and creativity.